Strong association between smoking and the risk of revision in a cohort study of patients with metal‐on‐metal total hip arthroplasty. Issue 6 (24th February 2014) - Lübbeke, Anne; Rothman, Kenneth J.; Garavaglia, Guido; Barea, Christophe; Christofilopoulos, Panayiotis; Stern, Richard; Hoffmeyer, Pierre
ABSTRACT Thus far the ability to predict who will develop early failure following the insertion of a metal‐on‐metal (MoM) bearing has been very limited. Our objective was to assess the effect of smoking on failure rates in patients with MoM bearing, compared with patients with ceramic‐on‐polyethylene (CoP) bearing. From a prospective hospital‐based registry we included all primary THAs operated upon between 1/2001 and 12/2011 with MoM or CoP bearings of the same cup design and head size (28 mm). We compared revision rates through 10/2013 classified by smoking status and type of bearing. We included 1, 964 patients (median age 71, 57% women), 663 with MoM and 1, 301 with CoP bearing. Mean follow‐up was 6.9 years (range 1.8–12.8). Revisions were required for 56 THAs. In patients with MoM bearing the adjusted incidence rate of revision among ever‐smokers was four times greater than among never‐smokers (95% CI 1.4–10.9). Among those with CoP bearing, the rate ratio was only 1.3 (95% CI 0.6–2.5). We found a strong association between smoking and increased failure of MoM THAs. In contrast, the association was weak for patients with CoP bearing. Smoking might be a trigger or an effect amplifier for adverse reactions to metal debris from MoM bearings. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:762–768, 2014.